Istota dylematu tożsamościowego zaufanie vs ryzyko we współczesnej rzeczywistości społeczno-kulturowej - Peret-Drążewska, Paulina (Studia Edukacyjne, 2020)
The aim of this article is the theoretical analysis of the situation of an individual existing in contemporary socio-cultural reality in the context of identity dilemmas, trust and risk. Considerations have been made about the nature of such categories as trust, risk, anxiety, and a sense of ontological security. This is not without significance for the quality of the condition of modern man, which also implies the need for the reconsideration of and pedagogical activities in the field of education and socialization of individuals participating in contemporary socio-cultural reality.